2013
DOI: 10.2478/pjct-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Natural Gas Fueling Station Reservoirs Pressure Based on Ideal Gas Model

Abstract: At CNG fuelling station, natural gas is usually stored in a cascade storage system to utilize the station more effi cient. The cascade storage system is generally divided into three reservoirs, commonly termed low, medium and high-pressure reservoirs. The pressures within these three reservoirs have huge effects on the performance of a CNG fuelling station and a fast fi lling process of natural gas vehicle's (NGV) cylinder. A theoretical analysis is developed to study the effects of the reservoirs pressures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…As is shown in this figure growth rate for temperature at the beginning of the process is higher for the buffer storage system. The same trend in the temperature profile has been seen in previse studies (FarzanehGord et al, 2011(FarzanehGord et al, , 2007(FarzanehGord et al, , 2008Kountz, 1994;Deymi-Dashtebayaz et al, 2012;Farzaneh-Gord et al, 2012a;Farzaneh-Gord and Deymi-Dashtebayaz, 2013;Farzaneh-Gord et al, 2012b, 2014. The final temperature of the actual conditions may be less than the modeling value.…”
Section: Simulation Resultssupporting
confidence: 69%
“…As is shown in this figure growth rate for temperature at the beginning of the process is higher for the buffer storage system. The same trend in the temperature profile has been seen in previse studies (FarzanehGord et al, 2011(FarzanehGord et al, , 2007(FarzanehGord et al, , 2008Kountz, 1994;Deymi-Dashtebayaz et al, 2012;Farzaneh-Gord et al, 2012a;Farzaneh-Gord and Deymi-Dashtebayaz, 2013;Farzaneh-Gord et al, 2012b, 2014. The final temperature of the actual conditions may be less than the modeling value.…”
Section: Simulation Resultssupporting
confidence: 69%
“…It was also found that ambient temperature influences the filling process and storage capacity (Shipley, 2002). Farzaneh-Gord et al (2007, 2008a, 2008b, 2012b, 2012c, 2013b have also simulated the fast filling process of CNG in several studies. The results indicated that ambient temperature has considerable effects on the filling process and final cylinder conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingtothe17thChinainternationalNGVsandgasstationequipmentexhibition&summit forum[1],thereare5,030,000NGVsontheroadinChina,withover4,800,000CNGVs,andover 4,700CNGfillingstations.BoththenumbersofCNGVandCNGfillingstationsaretopoftheworld. Obviously,forCNG'scheaperandfeweremissionthangasoline,thereisroomforsignificantgrowth worldwideandinChina.However,CNGVsrequireagreateramountofspaceforfuelstorage [2,3]. TheonboardstoragecapacityofNGVislimited.InChina,afullyfilledtankofCNGVcanrunabout 200km.Therefore,aCNGVdriverhastorefuelthenaturalgaspoweredvehiclefrequently.Butthe numberofCNGsecondaryfillingstationsislimitedanditseffectivenessisneedtobeimproved.In Tianjin,CNGVdriversneedtowaitmorethan2hourstofillupthenaturalgasvehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore,toimprovetheCNGrefuelingeffectivenessisnecessaryandimportant,andalotof studieshavebeendone [2][3][4][5][6].Abibliography [7] …”
Section: Introductionmentioning
confidence: 99%